THE EFFECTS OF MOTOR THERAPY FOR THE INTELLECTUAL DISABILITY: A SYSTEMATIC REVIEW - Fadjaritha, Feby; Pratisti, Wiwien Dinar (Jurusan Pendidikan Luar Biasa, 2021)
This study aims to obtain an overview of the effect of motor therapy for children with mental retardation that has been empirically proven. The research approach uses the PRISMA systematic review and uses Harzing's Publish or Perish 7 application in article search. Eleven articles were found that aim to improve gross and fine motor skills in mentally retarded children. A total of approximately 84 mentally retarded children who became the subject of the study. The result is that there are 10 interventions that are proven to improve the motor skills of mentally retarded children and 1 intervention has no effect on increasing the motor skills of mentally retarded children.